Rethinking the Contemporary Discourse of Jihād - Hasnan Bachtiar; Luciana Anggraeni; Muhammad Asep (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2019)
The purpose of this article is to evaluate the phenomenon of combative jihadism domination and the associated conditioning factors. Also, it evaluates the possibility of jihād’s dominant concept being paralleled to the Western concept of ‘just war.’ It can be argued that Islam normatively recognizes two forms of jihād, namely the greater form, which is for self-purification and improvement, as well as the lesser jihād for combative war. Although the combative meaning has historically dominated the contemporary discourse of jihād, it has been conditioned by several factors. These factors include the growth of the radical Islamism ideology, Western hegemonic behavior, globalization, and the absence of alternative narratives. Furthermore, it was discovered that the dominant concept of jihād in a legalistic view, is relatively similar to the Western concept of ‘just war,’ which in reality tends to be illegal or “breaks the law.” It also discusses the normative and historical meanings of jihād, the factors that conditioned the domination of combative jihadism, and the concept of ‘just war’.